track2KBA: An R package for identifying important sites for biodiversity from tracking data - Beal, Martin (2021)
Abstract 1. Identifying important sites for biodiversity is vital for conservation and management. However, there is a lack of accessible, easily applied tools that enable practitioners to delineate important sites for highly mobile species using established criteria. 2. We introduce the R package ‘track2KBA’, a tool to identify important sites at the population level using tracking data from individual animals based on three key steps: (a) identifying individual core areas, (b) assessing population-level representativeness of the sample and (c) quantifying spatial overlap among individuals and scaling up to the population. 3. We describe package functionality and exemplify its application using tracking data from three taxa in contrasting environments: a seal, a marine turtle and a migratory land bird. 4. This tool facilitates the delineation of sites of ecological relevance for diverse taxa and provides output useful for assessing their importance to a population or species, as in the Key Biodiversity Area (KBA) Standard. As such, ‘track2KBA’ can contribute directly to conservation planning at global and regional levels.